Green Technologies in Business and Management practices in India (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Green technology means greater adoption of computing practices in business and managerial areas to improve our environmental friendly. Green technology should be used to operate computers and related by-products to reduce carbon footprint. It is only through green technology that we can keep our environment safe and balanced as well as help in reducing human impact on the environment and creating sustainable development methods. There are three major parameters of green technology such as social equitability, economic feasibilityand sustainability. Our current actions are pulling the world towards and ecological disaster which if happens would make our life imbalance.This paper proposes its focus towards green technology in business and management practices in the organization for the practical implementation on changes that can result in more energy efficient consumption by the system. One of the most challenging goals in our day to day practices is to reduce carbon emissions and control temperature rise which can be addressed by the use of green technologies such as green buildings, fuel efficient transportation, paperless offices, sustainable manufacturing, energy efficiency measures, waste recycling etc. Green technologies benefits are immense. Green technologies are an approach towards saving our livelihood in this earth and are necessary if we want to live on this earth beyond upcoming centuries. Green technologies guide us a way out of destruction. Solutions are discussed in terms of technology and economic evidence proofing the benefits of going green.